Care trajectories are associated with quality improvement in the treatment of patients with uncontrolled type 2 diabetes: A registry based cohort study. Issue 5 (October 2015) - Goderis, Geert; Van Casteren, Viviane; Declercq, Etienne; Bossuyt, Nathalie; Van Den Broeke, Carine; Vanthomme, Katrien; Moreels, Sarah; Nobels, Frank; Mathieu, Chantal; Buntinx, Frank
Highlights: Care trajectory patients show poor glycaemic control and severe co-morbidity. Yet, these patients already received better follow-up and more intense treatment. Care trajectories selected a group of patients in need of intensive shared care. Enrolment in a care trajectory intensified both treatment and follow-up. Abstract: Aims: To analyse whether care trajectories (CT) were associated with increased prevalence of parenteral hypoglycemic treatment (PHT = insulin or GLP-1 analogues), statin therapy or RAAS-inhibition. Introduced in 2009 in Belgium, CTs target patients with type 2 diabetes mellitus (T2DM), in need for or with PHT. Methods: Retrospective study based on a registry with 97 general practitioners. The evolution in treatment since 2006 was compared between patients with vs. without a CT, using longitudinal logistic regression. Results: Comparing patients with ( N = 271) vs. without a CT ( N = 4424), we noted significant differences ( p < 0.05) in diabetes duration (10.1 vs. 7.3 years), HbA1c (7.5 vs. 6.9%), LDL-C (85 vs. 98 mg/dl), microvascular complications (26 vs. 16%). Moreover, in 2006, parenteral treatment (OR 52.1), statins (OR 4.1) and RAAS-inhibition (OR 9.6) were significantly more prevalent ( p < 0.001). Between 2006 and 2011, the prevalence rose in both groups regarding all three treatments, but rose significantly faster ( p < 0.05) after 2009 in the CT-group. Conclusions: Patients enrolled in a CT differ from other patients even before the start of this initiative with more intense hypoglycemic and cardiovascular treatment. Yet, they presented higher HbA1c-levels and more complications. Enrolment in a CT is associated with additional treatment intensification.